The role of risk management in the Gulf Colleges of Administrative and Human Sciences in limiting the effects of the Corona pandemic (COVID 19) on university education - Elhag, Noureldaim Eltayeb Yousif (Journal of Risk and Crisis Management, 2021)
The study aimed to know the effect of risk management in the Gulf Colleges of Administrative and Human Sciences in limiting the effects of the Corona pandemic on university education. The importance of the study lies in the possibility of benefiting from the results of this study in the application of risk management in the Gulf Colleges of Humanities for Administrative Sciences to reduce the effects of the Corona pandemic on university education. The study followed the descriptive approach, the analytical approach and the case study method, with the use of the (spss) program to analyze the data collected by the questionnaire tool from the number (55) random sample from the study population. Many conclusions were reached, most notably are: Gulf College risk management is working to evaluate emergency plans and rapid response to emergency situations to the Corona pandemic (COVID 19), and there is a relevant relationship with statistical evidence between the risk management in the Gulf Colleges of Administrative and Human Sciences and reducing the effects of the Corona pandemic on university education. The study recommended being necessary for establishing a specialized risk management department in the Gulf Colleges within the college’s organizational structure that includes competent and qualified risk management.